Visual selection for seed yield in the F2 and F3 generations of nine common bean crosses - PATINO, H.; Singh, S.P. (1989)
The effect of visual screening for grain yield was studied in 9 bean populations resulting from 3 different crossings (single, 3- way, and modified-double crosses) involving different groups of genetic pools from Central America and the Andes. The best yielding lines in the F2 and F3 generations were visually selected. A total of 149 selected lines, 9 plants discarded from each generation (F2 and F3), 23 parents, and 6 checks were evaluated in a partially balanced 14 x 14 lattice with 3 replications. A significant difference in yield was observed among the parents, selected lines, and the check; however, comparing the mean production of the selected lines with those discarded in F2 and F3, the line production, and the parent with the highest yield, visual selection was not effective in any crossing. (CIAT)